The significant clinical correlation of the intratumor oral microbiome in oral squamous cell carcinoma based on tissue-derived sequencing - Li, Zhengrui; Fu, Rao; Wen, Xutao; Wang, Qi; Huang, Xufeng; Zhang, Ling (Frontiers in Physiology, 2023)
Background: The microbiota is a critical component of the complex human microenvironment, impacting various physiological processes and disease development via the microbe–host interaction. In particular, the oral microbiota profoundly affects tumor development and progression. There is increasing evidence that oral microbiota is associated with the development of oral cancer, especially oral squamous cell carcinoma (OSCC). Methods: We comprehensively analyzed the oral microbiota in 133 OSCC samples worldwide. Subsequently, we evaluated the microbial compositions between OSCC patients and healthy people and their correlation with clinical parameters. The value of the oral microbiota as a diagnostic and prognostic biomarker was also determined. Results: This study found differences in critical oral microbiota between OSCC and normal controls. The most notable differences are present in p_Firmicutes, p_Actinobacteria, c_Fusobacteriia, o_Fusobacteriales, f_Fusobacteriaceae, and g_Fusobacterium. All six-level oral microorganisms were also associated with the clinical characteristics of OSCC, particularly with the clinical outcomes (survival time and status). We developed a predictive model based on this. We found that five different oral microorganisms have high confidence and can be used for clinical diagnosis and prognostic prediction, except for p_Actinobacteria. Conclusion: This study revealed that the intratumor oral microbiota of OSCC patients worldwide and the microbial signatures of OSCC patients possess similar properties in different regions, further refining the shortcomings of the current research field. We revealed that the oral microbiota could be used as a biomarker to reflect human health and disease progression status. This will provide new directions for tumor microbiome research. This means we can develop strategies through diet, probiotics, and antibiotics for cancer prevention and treatment.